Riskante Leben? Geschlechterordnungen in der Reflexiven Moderne - Moser, Vera; Rendtorff, Barbara (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2012)
Individualisation processes and the redistribution of social risks do not leave traditional gender relations untouched. The contributions in this volume examine the changes that (can) arise for gender identities, gender relations and gender-typical positioning in society.